Universal Design for Individual Differences - Meyer, Anne; Rose, David H. (Educational Leadership, 2000)
Contends that the principles of universal design when applied to instruction can guide the development of educational tools to accommodate the diverse needs of students. Nature of brain activity of individuals performing a given task; Development of the Universal Design for Learning tools and teaching strategies; How recognition processes occur in the brain.
Keywords: neurosciences